ETIKA KERJA KARYAWAN BAGIAN AKUNTANSI DALAM PERUBAHAN ORGANISASI BANK SYARIAH DI KOTA SEMARANG - Nikmatuniayah Nikmatuniayah; Resi Yudhaningsih; Hartono Hartono; Lilis Mardiana A. (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
This study aims to form a model of work ethics for employees in the accounting department in organizational change at Islamic banks. Specifically, this study aims to investigate the implementation of the work ethic of employees in the accounting department in organizational change in the Islamic banking environment in the city of Semarang. In the second year, the research was continued to design a decision making model for the internal accountant of Islamic banks. The work ethic is measured by using parameters: cognitive ability, affective component, and behavioral component. The hypothesis is formulated as follows: (1) H1: Work ethic has a significant effect on the Cognitive dimension of the attitude of accounting employees in organizational change. (2) H2: Work ethic has a significant effect on the Affective dimension of the attitude of the accounting department employees in organizational change. (3) H3: Work ethic has a significant effect on the behavioral tendency dimension of accounting employees in organizational change. The sample of this research is the employees of the accounting or finance department of Islamic banks in the city of Semarang. Data was collected by means of a questionnaire sent to Islamic banks in the city of Semarang. The data was processed using SEM and PLS. The results of research on work ethics, in this case Islam, affect the cognitive, affective, and behavioral tendencies of employees in the accounting department in changing the organization of Islamic banks.